Which is the most appropriate parenting style for the adolescents' self-esteem among Acehnese people? - Izzatur Rusuli (HUMANITAS: Indonesian Psychological Journal, 2021)
Parenting is a process of how parents treat their children, and it has an essential role in the children's development comprehensively, including children's self-esteem. This research aimed to identify the parenting styles practiced by the Acehnese people, the level of adolescents' self-esteem in Aceh, and the correlation between four parenting styles and adolescents' self-esteem. A total of 368 junior high school students in Aceh participated in this research. The research instrument consisted of two questionnaires; to measure parenting styles and to measure adolescents' self-esteem. This study used Pearson correlation and ANOVA in data analysis. The results show that the authoritative style is the dominant parenting style applied in this study. Meanwhile, most of the adolescents' self-esteem levels are at a moderate level. The results also show that there is a significant correlation between the authoritative style and adolescents' self-esteem, as well as authoritarian style and permissive style, but the last two styles have a weak correlation. Meanwhile, there is no significant correlation between uninvolved style and adolescents' self-esteem. Based on the study results, it can be concluded that the optimum parenting style to develop self-esteem is the authoritative style among the four parenting styles.